High-yielding fodder production technology for Coastal Bangladesh (Bangla) - Ahmed, Sharif; Devnath, Manik; Islam, Md. Tariqul (International Rice Research Institute, 2025)
This knowledge product presents innovative high-yielding fodder production technologies to the multiple stress conditions of coastal Bangladesh. With increasing livestock demands and growing climate vulnerabilities, ensuring adequate access to quality fodder is essential for maintaining livestock productivity and supporting farmers' livelihoods. The approach emphasizes cultivating resilient, fast-growing fodder varieties suitable for the saline-prone and waterlogged environments typical of coastal areas. It highlights opportunities to enhance feed security through diversified fodder crops, as well as the potential for income diversification among farmers. The product also addresses key challenges such as salinity intrusion, limited land availability, and environmental stresses. It discusses strategies to overcome these challenges, including the use of salt-tolerant fodder varieties and innovative cultivation practices. Implementing these high-yielding fodder systems can improve livestock health, increase milk and meat production, and contribute to climate resilience. The knowledge product provides practical guidelines for farmers, extension workers, and policymakers to effectively scale up fodder cultivation. Promoting these technologies offers a pathway toward sustainable livestock systems, improved food security, and enhanced rural livelihoods in Bangladesh’s vulnerable coastal areas.